Graphene-polyvinyl alcohol polymer based saturable absorption at 2000 nm region - Nabihah Hussin; Asrul Izam Azmi; Mohd Rashidi Salim; Muhammad Yusof Mohd Noor; Ahmad Sharmi Abdullah; Michael David; Fauzan Ahmad; Mohd Haniff Ibrahim (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
A graphene-polyvinyl alcohol (PVA) composite saturable absorption is demonstrated at 2000 nm region. Graphene suspension is produced using low-cost electrochemical exfoliation process. The suspension is mixed with PVA host polymer in 1:1 ratio and left evaporated at room temperature which finally produced graphene-PVA thin film. Thulium doped fiber (TDF) gain medium has been shown to produce a stable Q-switched pulse with a highest repetition rate of 54 kHz, a short pulse duration of 2.89 µs, a maximum peak power of 16 mW, and an estimated maximum pulse energy of 49 nJ. Apparently, at 2000 nm region, superior performances of graphene-PVA composite have been recorded which was largely contributed by meticulous composite preparation and homogenous mixture with PVA host.